2019
DOI: 10.3390/jcm8010092
|View full text |Cite
|
Sign up to set email alerts
|

A Multicentre Study of Burnout Prevalence and Related Psychological Variables in Medical Area Hospital Nurses

Abstract: Background: Nursing burnout is an important problem that affects nurses’ wellness, the quality of care and the health institutions. Study aims were to estimate levels of burnout; to determine the phase of burnout experienced by nurses in the medical area; to analyse the relationship between burnout and personality and psychological factors. Methods: Quantitative, cross-sectional, multicentre study. Hospitals from eight cities were included. The study sample was n = 301 nurses, working in the medical area of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
91
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 62 publications
7
91
1
2
Order By: Relevance
“…The ProQOL (Professional Quality of Life) was the instrument used by the included studies for data collection because it includes elements that other burnout scales do not examine, like compassion fatigue [18]. Compassion fatigue is not measured in other burnout instruments widely used, like the Maslach Burnout Inventory [2,36] or the Copenhagen Burnout Inventory (CBI), which is centered on burnout related to person, work, and client treatment [37]. The ProQOL focuses on elements that detect the quality of life of the individual and how it is projected in different aspects of their life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ProQOL (Professional Quality of Life) was the instrument used by the included studies for data collection because it includes elements that other burnout scales do not examine, like compassion fatigue [18]. Compassion fatigue is not measured in other burnout instruments widely used, like the Maslach Burnout Inventory [2,36] or the Copenhagen Burnout Inventory (CBI), which is centered on burnout related to person, work, and client treatment [37]. The ProQOL focuses on elements that detect the quality of life of the individual and how it is projected in different aspects of their life.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the mentioned programs, the examination of new technologies for the prevention of burnout has been a novel proposal. Technologies, such as mobile applications, have been used with mindfulness, a very effective approach in reducing this syndrome [36]. The application offers a simple and flexible introduction to the practice of mindfulness and can also increase work commitment, job satisfaction, innovation and creativity, and self-efficacy [43].…”
Section: Discussionmentioning
confidence: 99%
“…Burnout syndrome arises from chronic exposure to stress‐provoking factors and is characterized by three dimensions: emotional exhaustion (EE); depersonalization (D); and low personal accomplishment (PA) (Maslach & Jackson, ). This syndrome has a negative impact on physical and mental health (Bagheri Hosseinabadi et al, ; McVicar, ; Salvagioni et al, ), decreases productivity and quality of care (Cañadas‐De la Fuente et al, ; Daigle, Talbot, & French, ; Dall'Ora, Griffiths, Ball, Simon, & Aiken, ; De la Fuente‐Solana et al, ; Hall, Johnson, Watt, Tsipa, & O'Connor, ; Ramirez‐Baena et al, ) and raises staffing costs due to increased sick time (Letvak, Ruhm, & Lane, ; Sarafis et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In view of these negative impacts, it is important to derive profiles of persons at risk of developing the syndrome, in order to facilitate its prevention and treatment. Accordingly, the factors that may influence the appearance and evolution of burnout must be identified (Gómez‐Urquiza et al ; Ramírez‐Baena et al ). In this respect, studies have shown that occupational variables such as professional experience, specialization, shift work, and job satisfaction may all be relevant (Vargas et al ).…”
Section: Introductionmentioning
confidence: 99%